Negative electrode for lithium secondary battery and lithium secondary battery including the negative electrode
The application of a primer coating layer with a specific composition addresses the volume expansion and adhesion issues in silicon-based lithium secondary batteries, enhancing energy density and cycle life by improving the adhesion and pore structure of the negative electrode.
Patent Information
- Application Number
- JP2024539354
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-22
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-22
AI Technical Summary
Lithium secondary batteries using silicon-based active materials face issues with volume expansion during charging and discharging, leading to reduced adhesion with the collector layer and decreased cycle life due to uneven lithium ion distribution and surface degradation.
A negative electrode structure with a primer coating layer containing a specific composition is applied to silicon-based active materials, enhancing adhesion and improving the pore structure, thereby maintaining capacity and cycle performance.
The primer coating layer improves the adhesion of silicon-based active materials to the collector layer, maintaining high energy density and capacity while extending the battery's cycle life by reducing surface degradation and diffusion resistance.
Smart Images

Figure 2025502788000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0076794, filed with the Korean Intellectual Property Office on June 23, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that utilizes such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.
[0007] In recent years, in response to the demand for high-density energy batteries, active research has been conducted on methods to increase capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, in the case of silicon-based compounds, which are high-capacity materials, they have a large capacity and excellent capacity characteristics compared to conventionally used graphite, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a decrease in capacity from the beginning. In addition, when silicon-based negative electrodes are repeatedly charged and discharged, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface degradation, so performance needs to be improved in terms of battery cycles.
[0008] In addition, when making an anode using silicon-based active material, it is important that the pore structure of the anode is simple, and it is known that the better the tortuosity of the pores in the anode using silicon-based active material, the better the diffusion resistance. However, if the porosity is infinitely increased to improve the tortuosity of the pores, the contact points with the anode current collector layer decrease, and the adhesion with the anode current collector layer decreases, causing detachment and other problems, resulting in a decrease in life characteristics.
[0009] Various studies are being conducted to solve the above problems, but there are limitations to their application because they may actually reduce battery performance, and there are still limitations to the commercialization of negative electrode batteries with a high content of silicon-based compounds. As the ratio of silicon-based active material contained in the silicon-based active material layer increases, reactions with lithium ions are concentrated on the surface of the negative electrode, causing damage to the silicon-based active material on the surface side, resulting in a problem of reduced life characteristics.
[0010] Therefore, even when a silicon-based compound is used as an active material, it is necessary to develop a lithium secondary battery that improves the tortuosity of the negative electrode voids during charge and discharge cycles and has excellent adhesion to the negative electrode current collector layer. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent Publication No. 2009-080971 Summary of the Invention [Problem to be solved by the invention]
[0012] In the case of the existing carbon-based negative electrode, there is no problem associated with volume expansion, and the porosity of the carbon-based negative electrode active material layer is adjusted, or the adhesive strength with the current collector layer is not an issue.
[0013] However, in order to ensure the capacity characteristics, the negative electrode was changed from a carbon-based active material to a silicon-based active material. Although the volume expansion problem of general silicon-based active materials (such as SiO) is more severe than that of carbon-based active materials, no problems were caused by this.
[0014] However, in recent years, pure silicon active materials have been used among silicon-based active materials in order to maximize capacity characteristics and ensure rapid charging. In this case, however, there has been a problem in that the volume expansion is intense and the life characteristics are reduced due to the phenomenon of detachment from the negative electrode current collector layer.
[0015] Therefore, the present application relates to a negative electrode for a lithium secondary battery, which uses a silicon-based active material in the negative electrode, and which can improve cycle performance by improving the tortuosity of the voids to prevent degradation of the electrode surface during charge and discharge cycles and by improving the adhesive strength with the negative electrode current collector layer. The present application also relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the negative electrode. [Means for solving the problem]
[0016] One embodiment of the present specification is a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a primer coating layer containing a primer coating layer composition provided on one or both surfaces of the negative electrode current collector layer; and a negative electrode active material layer provided on the opposite surface of the primer coating layer to the surface in contact with the negative electrode current collector layer. The negative electrode active material layer contains a negative electrode active material layer composition including a silicon-based active material, a negative electrode conductive material, and a negative electrode binder. The silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and contains 95 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material. The primer coating layer composition includes at least one selected from the group consisting of a binder and a conductive material. The porosity of the negative electrode active material layer is 50% or more, and the D50 particle size of the silicon-based active material contained in the negative electrode active material layer is 5 μm or more.
[0017] In another embodiment, a lithium secondary battery is provided, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
Advantages of the Invention
[0018] The negative electrode for a lithium secondary battery according to one embodiment of the present invention is characterized in that the active material layer has a single layer structure, the content of the silicon-based active material in the negative electrode active material layer is increased to increase the energy density of the negative electrode, and the ranges of the particle size and porosity of the silicon-based active material satisfy the ranges according to the present application, simplifying the pore structure and improving the tortuosity of the pores.
[0019] The negative electrode active material layer has a large volume expansion during charging and discharging, and may be detached from the negative electrode current collector as the cycles proceed, and the amount of the negative electrode conductive material and the negative electrode binder is minimized to realize a high energy density, which may reduce the contact points with the negative electrode current collector.The main object of the present invention is to solve these problems by coating a primer coating layer containing a primer coating layer composition having a specific composition and content on the top of the negative electrode current collector layer.
[0020] That is, the present invention is characterized in that it can maximize the high energy density and capacity characteristics, which are advantages of silicon-based negative electrodes, while solving the existing problems by adjusting the porosity range of the negative electrode active material layer and further improving the life characteristics by applying a primer coating layer.
[0021] In conclusion, the negative electrode for a lithium secondary battery according to the present invention is mainly characterized in that it has excellent output and life characteristics by using a silicon-based active material to maximize capacity characteristics, a negative electrode active material layer that satisfies a specific porosity range in order to simplify the pore structure, and a primer coating layer having a specific composition is used to improve adhesion to the negative electrode current collector. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Before describing the present invention, some terms will first be defined. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0024] In this specification, "p to q" means a range of "not less than p and not more than q". In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.
[0025] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.
[0026] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0027] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."
[0028] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.
[0029] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention belongs to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be embodied in various different forms and is not limited to the following description.
[0030] One embodiment of this specification is a negative electrode for a lithium secondary battery including a negative electrode current collector layer; a primer coating layer including a primer coating layer composition provided on one or both surfaces of the negative electrode current collector layer; and a negative electrode active material layer provided on the opposite surface of the surface of the primer coating layer in contact with the negative electrode current collector layer, wherein the negative electrode active material layer includes a silicon-based active material; a negative electrode conductive material; and a negative electrode active material layer composition including a negative electrode binder, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 <x <2), based on 100 parts by weight of the silicon-based active material, 95 parts by weight or more of the SiOx (x = 0) is included, the primer coating layer composition includes at least one selected from the group consisting of a binder; and a conductive material, the porosity of the negative electrode active material layer is 50% or more, and the D50 particle size of the silicon-based active material contained in the negative electrode active material layer is 5 μm or more. A negative electrode for a lithium secondary battery is provided.
[0031] The negative electrode for a lithium secondary battery according to the present application has the advantages of an electrode that applies a high content of silicon particles with a single layer of active material, and at the same time, to solve the problems of simplification of the negative electrode pore structure, improvement of the adhesion force with the negative electrode current collector layer, and output characteristics, which are the disadvantages in this case, it is characterized in that a primer coating layer having a specific composition is configured.
[0032] FIG 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a primer coating layer 20 and a negative electrode active material layer 10 on one side of a negative electrode current collector layer 30 can be seen, and although FIG 1 shows that the negative electrode active material layer and the primer coating layer are formed on one side, they may be included on both sides of the negative electrode current collector layer. When included on both sides, the primer coating layer may be formed on both sides or on one side of the negative electrode current collector layer.
[0033] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below. In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a primer coating layer provided on one or both sides of the negative electrode current collector layer; and a negative electrode active material layer provided on a side of the primer coating layer opposite to a side in contact with the negative electrode current collector layer.
[0034] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0035] In one embodiment of the present application, the negative electrode current collector layer may have a thickness of 1 μm or more and 100 μm or less.
[0036] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.
[0037] In one embodiment of the present application, the negative electrode active material layer includes a negative electrode active material composition containing a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.
[0038] In one embodiment of the present application, the silicon-based active material includes a silicon-based active material containing silicon particles having a silicon particle size distribution of 0.01 μm or more and 50 μm or less, and a negative electrode for a lithium secondary battery is provided in which the D50 particle size of the silicon-based active material contained in the negative electrode active material layer is 5 μm or more.
[0039] In one embodiment of the present application, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be contained in an amount of 95 parts by weight or more.
[0040] In one embodiment of the present application, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) is contained in an amount of 95 parts by weight or more, preferably 97 parts by weight or more, more preferably 99 parts by weight or more, and may be contained in an amount of 100 parts by weight or less.
[0041] In one embodiment of the present application, particularly pure silicon (Si) particles may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material can mean that, as described above, when the total amount of the silicon-based active material is 100 parts by weight, pure Si particles (SiOx (x = 0)) that are not bonded to other particles or elements are included within the above range.
[0042] In one embodiment of the present application, the silicon-based active material may consist of SiOx (x = 0).
[0043] The negative electrode for a lithium secondary battery according to the present application contains the above-mentioned silicon-based active material in the negative electrode active material layer, specifically, pure silicon particles containing 95 parts by weight or more of SiOx (x=0). In this case, when the pure silicon particles are contained in a high content, the capacity characteristic is excellent, and in order to solve the life reduction characteristic due to the simplified pore structure, the above problem is solved by including the primer coating layer according to the present invention.
[0044] Meanwhile, the average particle size (D50) of the silicon-based active material of the present invention may be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the first negative electrode active material is equal to or greater than the above lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the current density non-uniformity phenomenon during charging and discharging.
[0045] In particular, in the negative electrode for a lithium secondary battery according to the present application, the porosity of the negative electrode active material layer satisfies 50% or more.
[0046] The porosity control affects the overall composition and content of the negative electrode active material layer composition, and is mainly influenced by the D50 particle size of the silicon-based active material contained in the negative electrode active material layer composition.
[0047] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the silicon-based active material contained in the negative electrode active material layer has a D50 particle size of 5 μm or more.
[0048] In still another embodiment, the D50 particle size of the silicon-based active material contained in the negative electrode active material layer may be in the range of 6 μm or more, preferably 7 μm or more, more preferably 8 μm or more, and 15 μm or less.
[0049] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the silicon-based active material contained in the negative electrode active material layer has a D50 particle size of 8 μm or more and 15 μm or less.
[0050] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the porosity of the negative electrode active material layer is 60% or more and 90% or less.
[0051] In one embodiment of the present application, the porosity of the negative electrode active material layer may be 50% or more, preferably 60% or more, and may be 90% or less, preferably 80% or less.
[0052] By satisfying the above-mentioned particle size distribution and porosity ranges, the negative electrode for a lithium secondary battery according to the present application satisfies the above-mentioned range of porosity and simplifies the pore structure, thereby improving the phenomenon in which the reaction between lithium ions and silicon-based active materials is concentrated only on the surface, thereby improving diffusion resistance, and by including a primer coating layer of a specific composition, the adhesion to the negative electrode current collector layer is improved, thereby increasing the adhesion even when charge / discharge cycles are continued, thereby improving the life characteristics.
[0053] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET surface area is measured according to DIN 66131 (using nitrogen).
[0054] In one embodiment of the present application, the silicon-based active material can be, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or shard particles.Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be in the form of a silicon-containing film or coating.
[0055] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0056] In this application, the circularity is determined by the following formula 1, where A is the area and P is the perimeter. [Formula 1] 4πA / P 2
[0057] In one embodiment of the present application, the silicon-based active material may be 80 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
[0058] In another embodiment, the silicon-based active material may be 80 parts by weight or more, preferably 85 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition, and may be 99 parts by weight or less, preferably 97 parts by weight or less, and more preferably 95 parts by weight or less.
[0059] The negative electrode active material layer composition according to the present application has the effect of improving capacity characteristics by using a silicon-based active material having an extremely high capacity in the above-mentioned range, and in particular, by adjusting the range of the silicon-based active material contained in the negative electrode active material layer to the above-mentioned range, the problems of surface degeneration during charging and discharging, problems with life characteristics, and problems with securing a conductive path are solved without reducing the capacity performance of the entire negative electrode.
[0060] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix silicon-based compounds to increase capacity have been increasing. However, silicon-based compounds have a limitation in that their volume expands rapidly during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer and reducing the performance of the battery.
[0061] In addition, when a silicon-based active material of a certain particle size is included within the above range in order to adjust the porosity range as described above, a conductive path cannot be secured due to volume expansion during charging and discharging, resulting in a decrease in output characteristics and therefore a decrease in life characteristics.
[0062] Therefore, in one embodiment of the present application, the negative electrode conductive material may include at least one selected from the group consisting of a dot-like conductive material, a linear conductive material, and a sheet-like conductive material.
[0063] In one embodiment of the present application, the negative electrode conductive material may be any material that can be commonly used in the art without limitation, and may be selected from the group consisting of dot-shaped conductive materials, planar conductive materials, and linear conductive materials.
[0064] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity to the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.
[0065] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of 40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.
[0066] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0067] In one embodiment of the present application, the planar conductive material can increase surface contact between silicon particles in the negative electrode to improve conductivity, and at the same time, can suppress disconnection of the conductive path due to volume expansion, and can be expressed as a plate-shaped conductive material or a bulk-type conductive material.
[0068] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.
[0069] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in viscosity of the negative electrode slurry. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.
[0070] In one embodiment of the present application, the sheet conductive material provides a negative electrode composition having a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0071] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.
[0072] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, and it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.
[0073] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more.
[0074] In another embodiment, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.
[0075] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0076] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of 5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m2 / g or less.
[0077] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in a line with the longitudinal axes of the carbon nanotube units substantially aligned in the same direction or are entangled. The carbon nanotube units have a graphite sheet with a nano-sized diameter and a cylindrical shape with an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet. The bundled carbon nanotubes can be uniformly dispersed during the manufacture of the negative electrode compared to entangled type carbon nanotubes, and can smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0078] In one embodiment of the present application, the negative electrode conductive material may be 0.01 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0079] In another embodiment, the negative electrode conductive material may be 0.01 parts by weight or more and 40 parts by weight or less, preferably 0.1 parts by weight or more and 30 parts by weight or less, and more preferably 0.5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0080] In one embodiment of the present application, when the negative electrode conductive material contains only a linear conductive material, the content may be 0.01 parts by weight or more and 5 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0081] In yet another embodiment, when the negative electrode conductive material contains only a linear conductive material, the amount of the linear conductive material may be 0.01 parts by weight or more and 5 parts by weight or less, preferably 0.03 parts by weight or more and 3 parts by weight or less, and more preferably 0.1 parts by weight or more and 2 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0082] In one embodiment of the present application, the negative electrode conductive material includes dot-like conductive material; sheet-like conductive material; and linear conductive material, and the dot-like conductive material:sheet-like conductive material:linear conductive material may satisfy a ratio of 1:1:0.01 to 1:1:1.
[0083] In one embodiment of the present application, the dot-shaped conductive material may be in the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0084] In one embodiment of the present application, the sheet conductive material may satisfy the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0085] In one embodiment of the present application, the linear conductive material may satisfy the range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0086] In one embodiment of the present application, the negative electrode conductive material may include a linear conductive material and a sheet conductive material.
[0087] In one embodiment of the present application, the negative electrode conductive material may include a linear conductive material and a sheet conductive material, and the ratio of the linear conductive material:sheet conductive material may satisfy 0.01:1 to 0.1:1.
[0088] In one embodiment of the present application, the negative electrode conductive material particularly includes a linear conductive material and a planar conductive material, and by satisfying the above-mentioned composition and ratio, respectively, the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, and the number of points at which charging and discharging are possible increases, resulting in excellent output characteristics at a high C-rate.
[0089] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application serves to capture the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material serves to provide some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.
[0090] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0091] In one embodiment of the present application, the negative electrode binder may be included in an amount of 1 part by weight or more and 20 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0092] In another embodiment, the negative electrode binder may satisfy the range of 1 part by weight or more and 20 parts by weight or less, preferably 2 parts by weight or more and 15 parts by weight or less, and more preferably 3 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0093] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen of these substances is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0094] The negative electrode binder according to one embodiment of the present application plays a role in holding down the active material and conductive material in order to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the negative electrode silicon-based active material. Any common binder can be used as long as it fulfills the above role, and specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.
[0095] In one embodiment of the present application, the negative electrode current collector layer includes a primer coating layer comprising a primer coating layer composition provided on one or both sides thereof, and the primer coating layer composition may include at least one selected from the group consisting of a binder and a conductive material.
[0096] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the primer coating layer is 1 nm or more and 1 μm or less.
[0097] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the binder is present in an amount of 10 parts by weight or more and 100 parts by weight or less, based on 100 parts by weight of the primer coating layer composition.
[0098] The primer coating layer composition according to the present application may comprise a binder alone.
[0099] The primer coating layer composition according to the present application may include a binder and a conductive material.
[0100] In this case, the present application provides a negative electrode for a lithium secondary battery, in which the binder is present in an amount of 10 parts by weight to 100 parts by weight based on 100 parts by weight of the primer coating layer composition.
[0101] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the adhesive strength of a surface of the negative electrode active material layer in contact with the primer coating layer satisfies 100 gf / 5 mm or more and 500 gf / 5 mm or less under conditions of 25° C. and normal pressure.
[0102] In yet another embodiment, the adhesive strength of the surface of the negative electrode active material layer in contact with the primer coating layer may satisfy, at 25° C. and normal pressure conditions, 300 gf / 5 mm or more and 500 gf / 5 mm or less, preferably 300 gf / 5 mm or more and 450 gf / 5 mm or less, and more preferably 350 gf / 5 mm or more and 430 gf / 5 mm or less.
[0103] The adhesive strength was measured at 90° and a speed of 5 mm / s using a peel strength tester with 3M 9070 tape. Specifically, one surface of the negative electrode active material layer of the negative electrode for lithium secondary battery was adhered to one surface of a slide glass (3M 9070 tape) to which an adhesive film was attached. Then, the adhesive was attached by rolling it back and forth 5 to 10 times with a 2 kg rubber roller, and the adhesive strength (peel strength) was measured at an angle of 90° and a speed of 5 mm / s. At this time, the adhesive strength can be measured under conditions of 25°C and normal pressure.
[0104] Specifically, the adhesive strength was measured on a 5 mm x 15 cm electrode at 25°C and normal pressure.
[0105] In one embodiment of the present application, normal pressure may mean pressure in a state where no specific pressure is applied or reduced, and may be used in the same sense as atmospheric pressure. Generally, it may be expressed as 1 atmosphere.
[0106] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
[0107] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0108] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0109] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0110] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0111] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).
[0112] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0113] At this time, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these can be used alone or in mixture.
[0114] The positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0115] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0116] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0117] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0118] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with chain carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.
[0119] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:
[0120] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0121] The lithium secondary battery according to the present invention is useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs), and can be particularly preferably used as a constituent battery of a medium- to large-sized battery module. Thus, the present invention also provides a medium- to large-sized battery module including the above-mentioned lithium secondary battery as a unit cell.
[0122] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0123] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are intended to illustrate the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.
[0124] <Example> Preparation of the primer coating layer <Manufacture of the first primer coating layer> A PAM-based binder and SWCNT as a conductive material were dissolved in water at a weight ratio of 95:5 to obtain a slurry for forming a primer coating layer. In this case, 1.5 times as much CMC as SWCNT was used as a dispersant (solid content: 5%).
[0125] Next, the slurry for forming the primer coating layer was applied to both sides of a copper foil (Cu foil) collector having a thickness of 8 μm to a thickness of 0.5 μm, and then vacuum dried at 120° C. for 24 hours to form a negative electrode collector layer having a first primer coating layer.
[0126] <Manufacture of the second primer coating layer> A rubber-based (SBR) binder and Super-C (Carbon Black) as a conductive material were dissolved in a water:IPA=9:1 solvent at a weight ratio of 30:70 to obtain a slurry for forming a primer coating layer (solid content: 20%).
[0127] Next, the slurry for forming the primer coating layer was applied to both sides of a copper foil (Cu foil) current collector having a thickness of 8 μm to a thickness of 0.5 μm, and then vacuum dried at 120° C. for 24 hours to form a negative electrode current collector layer having a second primer coating layer.
[0128] <Production of negative electrodes> Example 1: Preparation of negative electrode A negative electrode active material layer composition was prepared by mixing silicon (average particle size (D50): 8 μm) as a silicon-based active material, SWCNT, and polyacrylamide as a binder in a weight ratio of 89:1:10. The negative electrode slurry was produced by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).
[0129] The mixing method was as follows: SWCNT, binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0130] The negative electrode slurry was applied at 2.75 mg / cm2 to both sides of a copper foil current collector having a thickness of 8 μm and having the first primer coating layer formed thereon as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer (thickness: 33μm) to prepare a negative electrode (porosity: 55%).
[0131] The battery was manufactured in the same manner as in Example 1, except that the negative electrode current collector layer and silicon-based active material in Table 1 below were used. [Table 1]
[0132] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0133] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0134] An electrolyte was injected between the positive electrode and the negative electrode of Example 1 via a polyethylene separator to prepare a secondary battery.
[0135] The electrolyte was prepared by adding 3% by weight of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 10:90, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0136] Monocells were prepared in the same manner as above, except that the negative electrodes of the Examples and Comparative Examples were used, and the life characteristics were evaluated in the range of 4.2-3.0V.
[0137] Experimental example 1: Life characteristic evaluation The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary batteries were subjected to a cycle test at 4.2-3.0 V, 1 C / 0.5 C, and the number of cycles at which the capacity retention rate reached 80% was measured.
[0138] Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100 The results are shown in Table 2 below.
[0139] Experimental example 2: Resistance increase rate measurement evaluation In the test of Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed.
[0140] Regarding the resistance increase rate measurement evaluation, data at 250 cycles was calculated, and the results are shown in Table 2 below. [Table 2]
[0141] As can be seen from Table 2, in the case of the negative electrode for a lithium secondary battery according to the present invention, the capacity characteristics are maximized by using a silicon-based active material, the negative electrode active material layer satisfies a specific porosity range in order to simplify the pore structure, and at the same time, a primer coating layer having a specific composition is used to improve adhesion to the negative electrode current collector, thereby demonstrating excellent output and life characteristics.
[0142] When the particle size (D50) of the existing silicon-based active material is large, the initial diffusion resistance can be improved, but the adhesion to the negative electrode current collector layer is insufficient, and as the cycle progresses, the resistance increases and the life characteristics deteriorate. In the embodiment of the present application, the particle size of the silicon-based active material can be made larger than that of the existing one by applying a primer coating layer.
[0143] In other words, compared to Comparative Example 6, in which the particle size was large and a primer coating layer was not applied, it was found that the life characteristics of Examples 1 to 5 were improved. In particular, when Comparative Example 6 was compared with Example 5, it was found that although the particle size was the same, there was a difference in life performance depending on whether or not a primer coating layer was present.
[0144] In Table 2, a resistance increase rate of >250 means that resistance measurement is not possible. Generally, resistance of 250% or more has a high R value, so when a current of 2.5C is applied, the device is turned off due to the upper safety voltage limit, making resistance measurement impossible.
[0145] In the end, in Comparative Examples 1, 2, 5, and 6, which do not include a primer coating layer like the present invention, it was confirmed that when a large particle size active material is used, the volume expansion is large, which causes a decrease in adhesion to the negative electrode current collector layer, resulting in increased resistance and a deterioration in life performance. On the other hand, in the case of the examples in which a primer coating layer is applied, the adhesion and diffusion characteristics are also improved, and it was confirmed that when a 5 μm silicon-based active material is applied, the performance characteristics are more excellent. [Explanation of symbols]
[0146] 10...Negative electrode active material layer 20 Primer coating layer 30 Negative electrode current collector layer
Claims
1. A negative electrode current collector layer, a primer coating layer including a primer coating layer composition provided on one or both surfaces of the negative electrode current collector layer; and a negative electrode active material layer provided on a surface of the primer coating layer opposite to a surface of the primer coating layer that contacts the negative electrode current collector layer; A negative electrode for a lithium secondary battery comprising: the negative electrode active material layer includes a negative electrode active material layer composition including a silicon-based active material, a negative electrode conductive material, and a negative electrode binder; The silicon-based active material includes one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the silicon-based active material includes 95 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material; The primer coating layer composition includes at least one selected from the group consisting of a binder and a conductive material, The negative electrode active material layer has a porosity of 50% or more; The negative electrode for a lithium secondary battery, wherein the silicon-based active material contained in the negative electrode active material layer has a D50 particle size of 5 μm or more.
2. The negative electrode for a lithium secondary battery according to claim 1 , wherein the thickness of the primer coating layer is from 1 nm to 1 μm.
3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer has a porosity of 60% to 90%.
4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material contained in the negative electrode active material layer has a D50 particle size of 8 μm or more and 15 μm or less.
5. The negative electrode for a lithium secondary battery according to claim 1 , wherein the silicon-based active material is 80 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
6. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode conductive material includes at least one selected from the group consisting of dot-like conductive materials, linear conductive materials, and sheet-like conductive materials.
7. The negative electrode for a lithium secondary battery according to claim 1 , wherein the binder is present in an amount of 10 parts by weight to 100 parts by weight, based on 100 parts by weight of the primer coating layer composition.
8. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the adhesive strength of the surface of the negative electrode active material layer in contact with the primer coating layer is 100 gf / 5 mm or more and 500 gf / 5 mm or less under conditions of 25° C. and normal pressure.
9. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
10. positive electrode, The negative electrode for a lithium secondary battery according to any one of claims 1 to 9, A separator provided between the positive electrode and the negative electrode; and electrolyte, A lithium secondary battery comprising:
Citation Information
Patent Citations
Manufacture of polymer electrolyte secondary battery
JP1997204937A
Nonaqueous secondary battery, and method for manufacturing the same
JP2006019309A
Negative electrode and secondary battery
JP2009252580A
Negative electrode for nonaqueous electrolyte secondary battery, method for producing the same, and nonaqueous electrolyte secondary battery
JP2013232323A
Method for manufacturing all-solid lithium ion secondary battery
JP2018181706A